A crime script analysis of counterfeit identity document procurement online - Holt, Thomas J. (Deviant behavior, 2022)
Over the last two decades, researchers explored various aspects of the operational practices of online illicit market operations through the Open and Dark Web for various physical and digital goods. Far less work has considered the presence of counterfeit identity documents for sale within these markets, or the process of advertising, purchasing, producing, selling, and delivering these materials. This study utilized a qualitative crime script analysis of 19 vendors advertising counterfeit documents on the Open and Dark Web, focusing on the advertising, actualization, and delivery of various products. The pricing for various document types and the locations they claim to reflect citizenship of were examined, along with the variations dependent on where the product was advertised. The findings demonstrated that the market for identity documents shared common practices to other online markets, highlighting the value of crime script analyses to understand the distribution of goods through illicit markets generally.